NILAI-NILAI PENDIDIKAN PADA KEHARMONISAN PERNIKAHAN BEDA USIA DALAM PERSPEKTIF ISLAM - Fathi (PROFETIK: Jurnal Mahasiswa Pendidikan Agama Islam, 2026)
Abstract Age-gap marriage has become an interesting phenomenon in modern Islamic society. This study aims to analyze the implementation of Sakinah, Mawaddah, wa Rahmah values in maintaining marital harmony among age-gap couples. Using a descriptive qualitative method with a case study approach, data were collected through in-depth interviews with Khalik Mudani (55) and Sri Saraswati (45), who have been married for 25 years. The findings reveal that marital harmony is not determined by age but by communication quality, emotional stability, and the application of Islamic values. Sakinah manifests as tranquility and acceptance, mawaddah as affection and empathy, and rahmah as compassion and forgiveness. Religious orientation and mutual understanding become the foundation for achieving a harmonious family regardless of age differences. Keywords: Age Difference Marriage; Couple Communication; Household Harmony; Islamic Values; Marriage Psychology; Non-Ideal Family; Sakinah Mawaddah Wa Rahmah